Konsep Keyakinan dalam Perbahasan Epistemologi Muslim Liberal dan Ahli Sunnah Wal Jamaah: The Concept of Certainty in the Epistemological Discourse in Liberal Muslims and Ahli Sunnah Wal Jamaah - Kamis, Maryam Habibah; Hamat, Mohd Fauzi; Wan Ramli, Wan Adli (Al-Basirah Journal, 2024)
Certainty is an important element in the definition of Islamic knowledge and epistemological debate. However, a survey of two schools of Islamic thought, namely liberal Muslims and Ahli Sunnah Wal Jamaah as presented by al-Baghdadi, found that each has a different conceptions of the meaning and position of certainty in the theory of knowledge. Certainty is one of the fundamental epistemological characteristics in the view of Ahli Sunnah Wal Jamaah. This article analyzes the comparison of the concept of certainty in the epistemological debates of liberal Muslims and Ahli Sunnah Wal Jamaah. This study uses a uses a data collection methods and data analysis methods. The results of the study found that the concept of certainty discussed by liberal Muslims is inconsistent and even at some point contrary to the epistemological thinking of Ahli Sunnah Wal Jamaah as presented by al-Baghdadi.